Technology of Quick-Frozen Flour Fish Culinary Products - Pavlova, Valentina; Saenkova, Irina; Shokina, Yulia; Shokin, Grigoriy (KnE Life Sciences, 2022)
In this article, the results of the development of the functional fish culinary product “Thorny Skate and Cod Pie” are presented. A traditional recipe was used for making the yeast dough for the pie. The pie filling recipe was designed using Fuzzy Logic in the Matlab software package.Optimized parametersfor the selected sensory evaluation of the pie were calculated. On the basis of a priori information, key components of the filling (including the fraction of the fish components and skate meat) were chosen as the factors of interest. According to the simulation results, the optimal values werea 50/50 percentage for the first and the second factor respectively, and this providedthe maximum organoleptic assessment (five points on a five-point scale). The simulation results were compared with the results of the organoleptic evaluation of the pie made according to the optimized recipe, and their sufficient convergence was shown. The indicators of mass fraction of amine nitrogen and nitrogen of volatile bases was studied, as well as the microbiological safety indicators of flour fish culinary products, in accordance with the requirements of the Technical Regulations of the Eurasian Economic Union 040/2016 ”On the safety of fish products”. The results showed a high efficiency of the shock freezing of the semi-finished product, brought to semi-readiness, for long-term storage (120 days at a temperature no higher than minus 18 ∘C), without reducing the quality or safety of the pie. The product had a cholesterol content from 220 to 260 mg%, which allowed it to be classified as functional. The nutritional values of the product (mass fraction of protein, fat, carbohydrates, and amino acid composition) are presented. Keywords: thornyskate, functional product, pie with thornyskate and cod, shock freezing